Effect of supply chain structure and power dynamics on R&D and market performances - Yoo, Seung Ho; Seo, Yong Won (Journal of Business Economics and Management, 2017)
This study is the first investigating the effect of supply chain structure and players’ power dynamics on a supply chain’s R&D and market performances. We consider a three-stage supply chain, consisting of a R&D firm, a manufacturer, and a seller. We develop six supply chain models based on various structures and power dynamics, and reveal important implications by comparing the models. R&D performance is a function of supply chain structure; an integrated supply chain can expect improved performance. The selling price is a function of power dynamics, and is higher when R&D has bargaining power. Market and profit performances are higher in an integrated, manufacturer-led supply chain. The manufacturer’s role must be revisited; due to its location in the middle of the supply chain, the manufacturer can directly control the overall chain. On the other hand, a R&D firm could innately be associated with marginalization issues. Therefore, it is important for the R&D firm to have a systematic understanding of the entire system. This study contributes to the literature and practice by not only bridging the gap in the previous studies but also offering important managerial implications.